Atomizing ceramic disc and preparation method thereof
By superhydrophobic coating modification and femtosecond laser etching on the surface of the ceramic disc, a heterogeneous wetting boundary was formed, which solved the problem of poor atomization effect due to the lack of wetting on the surface of the traditional ceramic disc, and achieved a smaller atomization droplet particle size and better atomization effect.
Patent Information
- Application Number
- CN202411961246.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
Due to the limitations of surface characteristics and processing technology, traditional ceramic discs are hydrophobic and lack wetting properties, resulting in large particle sizes of atomized droplets and poor particle sizes, which affects the atomization effect.
By modifying the surface of the ceramic disc with superhydrophobic coating and etching the surface of the ceramic disc according to the preset pattern using femtosecond laser to form a superhydrophilic pattern area and a superhydrophobic boundary area, an atomized ceramic disc with heterogeneous wetting boundary was prepared.
The superhydrophilic area effectively inhibits the premature rupture of the liquid film, and the superhydrophobic boundary area can reduce the adhesion of the liquid, and work together to significantly reduce the particle size of the atomized droplets and improve the atomization effect.
Smart Images

Figure CN119707533A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of super-hydrophobic and super-hydrophilic surface regulation and preparation, and in particular to an atomized ceramic disc and a preparation method thereof. Background Art
[0002] Ceramic materials are widely used in agricultural atomizers, fabric dye spraying, and centrifugal atomizer discs for metal melt granulation due to their good chemical corrosion resistance, high mechanical strength, and excellent heat resistance.
[0003] However, due to the limitations of their surface characteristics and processing technology, traditional ceramic discs are usually hydrophobic and lack wettability. As a result, the ceramic surface cannot effectively regulate the atomized droplets, resulting in a larger particle size and poor particle size uniformity of the atomized droplets, which affects the atomization effect. Although there have been studies on related hydrophilic ceramic discs, the liquid will spread into a liquid film on the surface of the disc, and then break into droplets from the edge for atomization. However, the characteristics of the hydrophilic surface will cause the liquid film to rupture prematurely, resulting in areas on the surface of the disc that are not covered by the liquid film, resulting in extremely uneven distribution of the liquid film on the surface of the disc, which in turn deteriorates the atomization performance.
[0004] Therefore, the atomized ceramic disc still needs further research and improvement to overcome the current technical challenges. Summary of the invention
[0005] In view of this, the main purpose of the present disclosure is to provide an atomizing ceramic disc and a preparation method thereof, in order to at least partially solve at least one of the above-mentioned technical problems.
[0006] To achieve the above purpose, the technical solution of the present invention is as follows:
[0007] In one aspect of the present disclosure, a method for preparing an atomized ceramic disc is provided, comprising:
[0008] The surface of the ceramic disc is modified by using a super-hydrophobic coating to obtain a super-hydrophobic ceramic disc;
[0009] The surface of a super-hydrophobic ceramic disc is etched according to a preset pattern by a femtosecond laser to form a super-hydrophilic pattern area and a super-hydrophobic boundary area, thereby preparing an atomized ceramic disc with a heterogeneous wettability boundary.
[0010] In another aspect of the present disclosure, an atomized ceramic disc prepared by the above preparation method is provided, wherein the atomized ceramic disc has a super-hydrophilic pattern region and a super-hydrophobic boundary region.
[0011] According to an embodiment of the present disclosure, a method for preparing an atomized ceramic disc is provided, wherein the surface of the ceramic disc is modified by a super-hydrophobic coating to obtain a super-hydrophobic ceramic disc, and then the surface of the ceramic disc is etched according to a preset pattern area using femtosecond laser etching technology to obtain a super-hydrophilic pattern area of a micro-nano structure. The surface of the ceramic disc is provided with a super-hydrophilic pattern area and a super-hydrophobic boundary area at the same time, forming an atomized ceramic disc with a heterogeneous wettability boundary. The super-hydrophilic area effectively inhibits the premature rupture of the liquid film, while the super-hydrophobic boundary area can reduce liquid adhesion, and the two work together to significantly reduce the particle size of the atomized droplets and improve the atomization effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a flow chart of the method for preparing an atomized ceramic disc in Example 1 of the present disclosure;
[0013] Figure 2 It is the pattern preset in Embodiment 1 of the present disclosure;
[0014] Figure 3 Schematic diagram of an atomized ceramic disk with a zigzag heterogeneous wettability boundary prepared in Example 1 of the present disclosure;
[0015] Figure 4 This is a static contact angle test diagram of the super-hydrophobic boundary area of the atomized ceramic disc prepared in Example 1 of the present disclosure;
[0016] Figure 5 This is a static contact angle test diagram of the super-hydrophilic pattern area of the atomized ceramic disc prepared in Example 1 of the present disclosure;
[0017] Figure 6 A scanning electron microscope image of the super-hydrophilic pattern area of the atomized ceramic disc prepared in Example 1 of the present disclosure;
[0018] Figure 7 This is a diagram of the atomization effect of the atomizing ceramic disc in Example 1 and Comparative Examples 1-2 of the present disclosure at the critical flow rate and rotation speed that reach the fiber splitting mode;
[0019] Figure 8 This is a data graph of average particle size of atomized droplets of the atomized ceramic disc in Example 1 and Comparative Examples 1-2 of the present disclosure at the critical flow rate and rotation speed that reach the fibrous splitting mode. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.
[0021] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.
[0022] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0023] Ceramic materials are widely used in centrifugal atomizer discs in agricultural atomizers, fabric dye spraying, metal melt granulation, etc. due to their excellent chemical corrosion resistance, high mechanical strength and good heat resistance. However, due to the lack of wettability and reasonable structural design, traditional ceramic discs have large atomized droplet size and poor uniformity, which limits the further improvement of their atomization performance.
[0024] In the process of implementing the concept of the present disclosure, it was found that the hydrophilic modified ceramic disc can improve the wettability of the atomizing ceramic disc. However, during the centrifugal atomization process, the liquid will first spread into a liquid film on the surface of the disc, and then break into droplets from the edge. The hydrophilicity of the disc edge and sidewall causes the liquid to adhere, making the separated droplet size larger.
[0025] The present invention introduces a heterogeneous wettability edge structure with super-hydrophilic inner edge and super-hydrophobic outer edge on the surface of a ceramic disc through super-hydrophobic coating and femtosecond laser etching technology. The super-spreading performance of the liquid film on the super-hydrophilic surface is utilized to reduce the generation of surface "dry points" caused by premature rupture of the liquid film. At the same time, the super-hydrophobic edge can reduce the adhesion of the disc edge and sidewall to the liquid, reduce the particle size of the atomized separation droplets, and thus significantly improve the atomization effect of the atomized ceramic disc. In addition, the present invention can personalize the design and customization of the predetermined pattern of etching. By designing and setting the etching pattern and process parameters, the structure and atomization performance of the atomized ceramic disc can be changed to meet the needs of different application scenarios.
[0026] According to an embodiment of one aspect of the present disclosure, a method for preparing an atomized ceramic disc is provided, comprising:
[0027] The surface of the ceramic disc is modified by using a super-hydrophobic coating to obtain a super-hydrophobic ceramic disc;
[0028] The surface of a super-hydrophobic ceramic disc is etched according to a preset pattern by a femtosecond laser to form a super-hydrophilic pattern area and a super-hydrophobic boundary area, thereby preparing an atomized ceramic disc with a heterogeneous wettability boundary.
[0029] According to an embodiment of the present disclosure, a method for preparing an atomized ceramic disc is provided, and a ceramic disc is surface-modified by a super-hydrophobic coating to obtain a super-hydrophobic ceramic disc. The modification of the super-hydrophobic coating provides an initial hydrophobic surface for the ceramic disc, providing a basis for subsequent preparation. Subsequently, a femtosecond laser etching technique is used to etch a preset pattern area on the surface of the ceramic disc. A high-energy continuous femtosecond laser beam acts on the surface of the super-hydrophobic ceramic disc, which can instantly melt or even vaporize the surface material. The high-energy femtosecond laser will penetrate the super-hydrophobic coating, and form a micro-nano roughness on the ceramic surface of the lower layer, modifying the surface from super-hydrophobic to super-hydrophilic, and forming a super-hydrophilic pattern area with a micro-nano structure on the surface of the ceramic disc. The surface of the ceramic disc is made to have a super-hydrophilic area and a super-hydrophobic boundary at the same time, forming an atomized ceramic disc with a heterogeneous wettability boundary. During the atomization process, the super-hydrophilic pattern area can effectively promote the spreading and stabilization of the liquid film, reduce the premature rupture of the liquid film, and thus inhibit the generation of "dry points". At the same time, the super-hydrophobic boundary area helps to reduce the adhesion of the disk edge and sidewall to the liquid, further reducing the particle size of the atomized separated droplets and improving the uniformity of the particle size. The synergistic effect of the super-hydrophilic area and the super-hydrophobic boundary significantly reduces the particle size of the atomized droplets and improves the uniformity and efficiency of atomization. In addition, the heterogeneous wettability boundary also helps to promote the transformation of the centrifugal atomization mode from droplet splitting to fiber splitting mode. The fiber splitting mode can further improve the atomization effect because it can produce smaller atomized droplet size and narrower particle size distribution.
[0030] According to an embodiment of the present disclosure, the super hydrophobic coating comprises, by mass percentage:
[0031] The liquid adhesive is 1-1.5%, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc. The liquid adhesive can firmly adhere the hydrophobic SiO2 nanoparticles to the surface of the ceramic disc to form a stable super-hydrophobic layer. The liquid adhesive can be a commercially available liquid adhesive, for example, ST2000 adhesive can be used;
[0032] 1~3% of hydrophobic SiO2 nanoparticles, for example, 1%, 1.5%, 2%, 2.5%, 3%, etc., the hydrophobic SiO2 nanoparticles increase the surface roughness of the ceramic disc, thereby enhancing the hydrophobicity of the surface of the ceramic disc. In addition, the hydrophobic SiO2 nanoparticles can introduce perfluoroalkyl chains with low surface energy and hydrophobic long alkyl chains, further enhancing the hydrophobicity of the surface of the ceramic disc. The hydrophobic SiO2 nanoparticles can be selected from AEROSIL R202, with a particle size of 20~50nm;
[0033] The alcohol or ester solvent is 95.5-98%, for example, 95.5%, 96%, 96.5%, 97%, 98%, etc. The alcohol or ester solvent helps to adjust the viscosity and fluidity of the super-hydrophobic coating, making it easy to apply and evenly distribute. For example, ethanol (purity ≥ 99.7%) can be used as an alcohol solvent, and ethyl acetate (purity ≥ 99.7%) can be used as an ester solvent.
[0034] The liquid binder, the hydrophobic SiO2 nanoparticles and the alcohol or ester solvent total 100%.
[0035] According to an embodiment of the present disclosure, modifying a ceramic disc using a super-hydrophobic coating includes:
[0036] The ceramic disc is immersed in the super-hydrophobic coating for 1 min~5 min to form a super-hydrophobic layer on the surface of the ceramic disc, and then dried at 60℃~100℃ for 1 h~2 h to evaporate the solvent to obtain a super-hydrophobic ceramic disc modified with hydrophobic SiO2 nanoparticles. The thickness of the formed super-hydrophobic layer is 5~10 μm.
[0037] According to an embodiment of the present disclosure, the difference between the diameter of the ceramic disc and the diameter of the pattern area is 3 to 10 mm, for example, it can be 3 mm, 5 mm, 7 mm, 9 mm, 10 mm, etc., so that a superhydrophobic boundary area is left on the ceramic disc to form a heterogeneous wettability boundary.
[0038] According to an embodiment of the present disclosure, the preset pattern includes: any one of a sawtooth circle structure, a circular structure, a sharp blade structure, a gradually pointed blade structure, a blunt blade structure, and a rounded blade structure. The present disclosure can design and customize the preset pattern of etching. By designing and setting the etching pattern and process parameters, the atomization ceramic disc structure and the atomization performance can be changed to meet the needs of different application scenarios. Preferably, the preset pattern selects a sawtooth circle structure. Among them, the ratio of the circumference of the ceramic disc to the number of sawteeth in the sawtooth circle structure is 3~4:1, for example, it can be 3:1, 3.1:1, 3.4:1, 3.6:1, 3.8:1, 4:1, etc. Exemplarily, in the specific preparation process, the disc diameter can be 20mm~40mm, and the number of sawteeth in the sawtooth circle structure can be 18~36.
[0039] According to the embodiments of the present disclosure, etching an appropriate sawtooth circular structure in the atomizing disc can significantly improve the efficiency of liquid film separation and the uniformity of particle size. The sawtooth edge in the sawtooth circular structure can cause the liquid film to be separated at equal intervals at specific fixed positions on the edge of the disc, thereby ensuring that the droplet particle size generated between different separation positions is more uniform. In addition, the sawtooth edge also helps to optimize the centrifugal atomization mode, causing the original droplet splitting mode to transform into a fiber splitting mode. By etching and introducing a sawtooth wettability edge on the surface of the ceramic disc, not only the problem of difficult mechanical processing of the edge of the traditional sawtooth structure is overcome, and the atomization improvement effect of the traditional sawtooth structure is achieved, but also the problem of strong airflow disturbance caused by the edge of the traditional sawtooth structure during high-speed rotating atomization can be avoided, further improving the atomization effect.
[0040] Compared with ordinary circular atomizer discs, the centrifugal atomizer disc with a serrated heterogeneous wettability boundary has a serrated structure that can reduce the critical flow rate and rotation speed for forming a fibrous splitting mode. At the same time, the hydrophobic boundary of the heterogeneous wettability boundary can reduce the liquid film thickness and obtain a better atomization effect.
[0041] According to the embodiments of the present disclosure, the material of the ceramic disc is selected from any one of aluminum oxide, silicon nitride, silicon carbide, and zirconium oxide, preferably aluminum oxide. Aluminum oxide material has excellent high temperature resistance, corrosion resistance, high hardness and good electrical insulation performance, so that the disc can stably withstand high temperature and corrosive environment during atomization, while ensuring the wear resistance and long-term operation reliability of the disc. Most of the rotating discs currently used for centrifugal atomization are metal materials, and the disc processing method with a serrated structure edge is generally mechanical processing, and the manufacturing process is cumbersome, the processing accuracy is low, and it is not easy to carry out wettability modification. Alumina ceramic material not only has excellent heat resistance and high temperature stability, but also has good chemical stability, and is easy to carry out wettability modification, so the present disclosure preferably uses alumina ceramic disc as an atomizing disc. A centrifugal atomizing disc with a serrated heterogeneous wettability boundary is prepared by super hydrophobic coating and laser etching to modify the alumina ceramic disc.
[0042] According to the embodiments of the present disclosure, the static contact angle of the super-hydrophobic boundary area is 150-160°, for example, it can be 150°, 152°, 155°, 157°, 159°, 160°, etc. The larger static contact angle characteristic makes it difficult for droplets to adhere to the super-hydrophobic boundary area, effectively promoting the rapid separation of the liquid film. The static contact angle of the super-hydrophilic pattern area is 0-5°C, for example, it can be 0°, 1°, 2°, 3°, 4°, 5°, and the static contact angle characteristic close to 0° allows droplets to spread rapidly in the super-hydrophilic pattern area, thereby realizing an atomized ceramic disc with a heterogeneous wettability boundary.
[0043] According to an embodiment of the present disclosure, the hopping speed of the femtosecond laser is 200-500 mm / s, for example, 200 mm / s, 250 mm / s, 300 mm / s, 400 mm / s, 500 mm / s, etc.; the marking speed is 1000-3000 mm / s, for example, 1000 mm / s, 1500 mm / s, 2000 mm / s, 2500 mm / s, 3000 mm / s, etc.; the scanning pitch is 10-30 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc.; the turning delay is 5-20 μs, for example, 5 μs, 7 μs, 10 μs, 15 μs, 17 μs, 20 μs, etc.; the frequency is 500-1000 KHz, for example, 500 KHz, 600 KHz, 700 KHz, 800 KHz, 900 KHz, 1000 KHz, etc.; the power is 2~6 W, for example, 2 W, 3 W, 4 W, 5 W, 6 W, etc.; the number of scans is 5~10 times, for example, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times. In specific implementation, the wavelength of the femtosecond laser can be 355nm, the laser spot size is 30μm, and the pulse width is less than 500fs. By adjusting the parameters of the femtosecond laser, the etching time, depth and etching effect can be precisely controlled, so that the energy of the femtosecond laser is sufficient to etch away the super-hydrophobic layer, and at the same time, a micro-nano structure with super-hydrophilic properties is formed on the surface of the ceramic disc. In the specific preparation process, the etching depth of the femtosecond laser can be 6~12μm, and a super-hydrophilic pattern area is formed on the surface of the disc, while the super-hydrophobic boundary area is retained in the rest, so that an atomized ceramic disc with a significant heterogeneous wettability boundary is prepared, which improves the atomization performance.
[0044] According to the embodiments of the present disclosure, the thickness difference between the super-hydrophobic boundary area and the super-hydrophilic pattern area is 1-2 μm, for example, 1 μm, 1.2 μm, 1.5 μm, 1.7 μm, 1.9 μm, 2 μm, etc. By adjusting the parameters of the femtosecond laser, the thickness difference between the two areas is minimised, avoiding the appearance of obvious steps or height differences on the surface of the atomised ceramic disc. The smoothness of the disc surface is ensured, and the disturbance of the liquid film during the flow process is reduced, thereby improving the stability and efficiency of the atomisation process.
[0045] According to the embodiments of the present disclosure, in the specific preparation process, a centrifugal atomized alumina ceramic atomized disc with a serrated wettability edge can be prepared by combining super-hydrophobic coating and laser marking technology. Wherein super-hydrophobic coating refers to a coating having a water contact angle greater than 150° and a contact angle hysteresis less than 5° after coating a solid surface. The basic principle of laser marking is that a high-energy continuous laser beam is generated by a laser generator, and the focused laser acts on the material to be etched, causing its surface to melt instantly or even vaporize. Therefore, when a femtosecond laser acts on an alumina ceramic disc coated with a super-hydrophobic coating, the high-energy laser will penetrate the coating, and the alumina surface of the lower layer will form a micro-nano roughness, and the surface will be modified from super-hydrophobic to super-hydrophilic. By controlling the etching path of the laser on the surface of the material, a specific wettability edge can be formed.
[0046] According to an embodiment of another aspect of the present disclosure, an atomized ceramic disc prepared by the above preparation method is provided, and the atomized ceramic disc has a super-hydrophilic pattern area and a super-hydrophobic boundary area.
[0047] According to the embodiments of the present disclosure, the prepared atomized ceramic disc has a heterogeneous wettability boundary, the super-hydrophilic pattern area helps the liquid film to spread on the disc surface, and the super-hydrophobic boundary area helps to inhibit the premature rupture of the liquid film, thereby making the liquid film distribution more uniform. It can reduce the adhesion of the disc edge and sidewall to the liquid, thereby reducing the particle size of the atomized separated droplets and improving the uniformity of the particle size.
[0048] According to the embodiments of the present disclosure, the average particle size of the atomized droplets of the atomizing ceramic disc is 300-400 μm, for example, 300 μm, 320 μm, 350 μm, 370 μm, 400 μm. The prepared atomizing ceramic disc can effectively reduce the particle size of the atomized droplets, thereby effectively improving the overall efficiency and performance of the atomization system.
[0049] In order to make the purpose, technical scheme and advantages of the present disclosure clearer, the present disclosure is further described in detail below in conjunction with specific examples and drawings. Specific techniques or conditions not specified in the examples are all conventional methods, which can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. It should be noted that the methods provided in the present disclosure are all conventional methods unless otherwise specified, and the reactants and reagents can be obtained from public commercial channels unless otherwise specified.
[0050] Embodiment 1:
[0051] This embodiment 1 provides an atomizing ceramic disc. Figure 1 This is a flow chart of the method for preparing the atomized ceramic disc in Example 1 of the present disclosure, as shown in Figure 1 As shown, the three-dimensional preparation of the atomized ceramic disc in this embodiment 1 includes the following steps S1 to S4.
[0052] Step S1: Calculated by mass percentage, a super hydrophobic coating is obtained by mixing and configuring: 1.2% of ST200 adhesive, 2% of hydrophobic SiO2 nanoparticles (AEROSIL R202), and 96.8% of ethanol (purity ≥ 99.7%), totaling 100%.
[0053] Step S2: Immerse an aluminum oxide (Al2O3) ceramic disc with a diameter of 25 mm and a thickness of 0.5 mm in the super-hydrophobic coating for 1 min, take it out to dry, and put it in an oven at 80°C for 1 h to obtain a super-hydrophobic ceramic disc.
[0054] Step S3: Draw a preset pattern on a computer using drawing software. Figure 2 is the pattern preset in Embodiment 1 of the present disclosure, such as Figure 2 As shown, the preset pattern is a sawtooth circle structure, the inner diameter of the pattern is 20 mm, the outer diameter is 25 mm, and the number of teeth is 18. The pattern is imported into the laser marking machine, and the inside of the pattern is filled with a filling spacing of 10 μm.
[0055] Step S4: Set the femtosecond laser parameters: 200 mm / s idle speed; 2000 mm / s marking speed; 10 μm scanning interval; 10 μs turning delay; 500 KHz frequency; 3 W power; 5 scanning times. The super-hydrophobic surface of the Al2O3 ceramic disc was laser etched by femtosecond laser, the super-hydrophobic coating on the zigzag edge structure area was etched away, and a super-hydrophilic micro-nano structure was obtained in this area, and a centrifugal atomized ceramic disc P1 with a zigzag heterogeneous wettability boundary was prepared.
[0056] Figure 3 Schematic diagram of an atomized ceramic disk with a serrated heterogeneous wettability boundary prepared in Example 1 of the present disclosure.
[0057] like Figure 3 As shown, the black part is the super-hydrophobic boundary area, and the white part is the super-hydrophilic pattern area etched by femtosecond laser.
[0058] The static contact angle of the surface of the atomized ceramic disk prepared in Example 1 of the present disclosure was measured on a contact angle meter. Figure 4 This is a static contact angle test diagram of the super-hydrophobic boundary area of the atomized ceramic disk prepared in Example 1 of the present disclosure, Figure 5 This is a static contact angle test diagram of the super-hydrophilic pattern area of the atomized ceramic disc prepared in Example 1 of the present disclosure.
[0059] like Figure 4 As shown in Figure 2, the static contact angle of the superhydrophobic boundary area is 154.7°. Figure 5As shown, the static contact angle of the superhydrophilic pattern area is about 0°, meeting the requirements of heterogeneous wettability boundary.
[0060] Figure 6 3 are scanning electron microscope images of the super-hydrophilic pattern area of the atomized ceramic disc prepared in Example 1 of the present disclosure, wherein a is a scanning electron microscope image of the super-hydrophilic pattern area at a magnification of 0.50 K; b is a scanning electron microscope image of the super-hydrophilic pattern area at a magnification of 1.0 K; c is a scanning electron microscope image of the super-hydrophilic pattern area at a magnification of 5.0 K; d is a scanning electron microscope image of the super-hydrophilic pattern area at a magnification of 10.0 K.
[0061] like Figure 6 As shown, after the super-hydrophilic pattern area of the atomized ceramic disc is etched by femtosecond laser, a micro-nano structure with roughness is formed on the surface, making the pattern area have super-hydrophilic properties.
[0062] Example 2
[0063] This embodiment 2 provides an atomized ceramic disc, which includes the following steps S1 to S4:
[0064] Step S1: Calculated by mass percentage, a super hydrophobic coating is obtained by mixing and configuring: 1.2% of ST200 adhesive, 2% of hydrophobic SiO2 nanoparticles (AEROSIL R202), and 96.8% of ethanol (purity ≥ 99.7%), totaling 100%.
[0065] Step S2: Immerse an alumina ceramic disc with a diameter of 25 mm and a thickness of 0.5 mm in the super-hydrophobic coating for 1 min, take it out to dry, and put it in an oven at 80°C for 1 h to obtain a super-hydrophobic ceramic disc.
[0066] Step S3: Draw a preset pattern on a computer using drawing software. The preset pattern is a sawtooth circle structure with an inner diameter of 20 mm, an outer diameter of 25 mm, and 24 teeth. Import the pattern into a laser marking machine, and fill the inside of the pattern with a filling spacing of 10 μm.
[0067] Step S4: Set the femtosecond laser parameters: 200 mm / s idle speed; 1500 mm / s marking speed; 10 μm scanning interval; 10 μs turning delay; 600 KHz frequency; 4 W power; 6 scanning times. The super-hydrophobic surface of the Al2O3 ceramic disc was laser etched by femtosecond laser, the super-hydrophobic coating on the zigzag edge structure area was etched away, and a super-hydrophilic micro-nano structure was obtained in this area, and a centrifugal atomized ceramic disc P2 with a zigzag heterogeneous wettability boundary was prepared.
[0068] The static contact angle of the surface of the atomized ceramic disc prepared in Example 2 of the present disclosure was measured on a contact angle meter. The static contact angle of the super-hydrophobic boundary area was 152.1°, and the static contact angle of the super-hydrophilic pattern area was about 0°, meeting the requirements of heterogeneous wettability boundary.
[0069] Example 3
[0070] This embodiment 3 provides an atomized ceramic disc, which includes the following steps S1 to S4:
[0071] Step S1: Calculated by mass percentage, a super hydrophobic coating is obtained by mixing and configuring: 1.2% of ST200 adhesive, 2% of hydrophobic SiO2 nanoparticles (AEROSIL R202), and 96.8% of ethanol (purity ≥ 99.7%), totaling 100%.
[0072] Step S2: Immerse an alumina ceramic disc with a diameter of 25 mm and a thickness of 0.5 mm in the super-hydrophobic coating for 1 min, take it out to dry, and put it in an oven at 80°C for 1 h to obtain a super-hydrophobic ceramic disc.
[0073] Step S3: Draw a preset pattern on a computer using drawing software. The preset pattern is a sawtooth circle structure with an inner diameter of 20 mm, an outer diameter of 25 mm, and 30 teeth. Import the pattern into a laser marking machine and fill the inside of the pattern with a filling spacing of 10 μm.
[0074] Step S4: Set the femtosecond laser parameters: 200 mm / s idle speed; 1000 mm / s marking speed; 10 μm scanning interval; 10 μs turning delay; 800 KHz frequency; 5 W power; 10 scans. The super-hydrophobic surface of the Al2O3 ceramic disc was laser etched by femtosecond laser, the super-hydrophobic coating on the zigzag edge structure area was etched away, and a super-hydrophilic micro-nano structure was obtained in this area, and a centrifugal atomized ceramic disc P3 with a zigzag heterogeneous wettability boundary was prepared.
[0075] The static contact angle of the surface of the atomized ceramic disc prepared in Example 2 of the present disclosure was measured on a contact angle meter. The static contact angle of the super-hydrophobic boundary area was 152.9°, and the static contact angle of the super-hydrophilic pattern area was about 0°, meeting the requirements of heterogeneous wettability boundary.
[0076] Comparative Example 1
[0077] This comparative example 1 provides an untreated circular Al2O3 atomized ceramic disc D1.
[0078] Comparative Example 2
[0079] This comparative example 2 provides an Al2O3 atomized ceramic disc D2 with a sawtooth edge structure.
[0080] The atomization effect of the atomizing ceramic disc in Example 1 and Comparative Examples 1-2 of the present disclosure was tested: the atomizing ceramic disc was fixed on the atomizing motor, a syringe pump was used for liquid supply, and the centrifugal atomization process of the atomizing ceramic disc and the factors affecting the atomization performance were studied and analyzed using high-speed photography and a laser particle size analyzer.
[0081] Figure 7 These are atomization effect diagrams of the atomizing ceramic discs in Example 1 and Comparative Examples 1 to 2 of the present disclosure at the critical flow rate and rotation speed that reach the fibrous splitting mode, wherein a is the atomization effect diagram of the atomizing ceramic disc in Comparative Example 1 at the critical flow rate and rotation speed that reach the fibrous splitting mode; b is the atomization effect diagram of the atomizing ceramic disc in Comparative Example 2 at the critical flow rate and rotation speed that reach the fibrous splitting mode; c is the atomization effect diagram of the centrifugal atomizing disc in Example 1 at the critical flow rate and rotation speed that reach the fibrous splitting mode.
[0082] like Figure 7 As shown, the atomized ceramic discs in Example 1 and Comparative Examples 1-2 of the present disclosure reach the critical flow rate (31 ml·min -1 By comparing the atomization effects of the three atomizing ceramic discs at 2000 rpm and 2000 rpm, it can be observed that the droplets on the atomizing ceramic disc in Example 1 of the present disclosure can achieve an excellent fibrous splitting pattern.
[0083] Figure 8 This is a data graph of average particle size of atomized droplets of the atomized ceramic disc in Example 1 and Comparative Examples 1-2 of the present disclosure at the critical flow rate and rotation speed that reach the fibrous splitting mode.
[0084] like Figure 8 As shown, the atomized ceramic discs in Example 1 and Comparative Examples 1-2 of the present disclosure reach the critical flow rate (31 ml·min -1 ) and the rotation speed (3000rpm), it can be observed that the average particle size of the atomized droplets on the atomized ceramic disc in Example 1 of the present disclosure is significantly reduced, the particle size distribution is narrow, and a better atomization effect is exhibited.
[0085] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.
Claims
1. A method for preparing an atomized ceramic disc, characterized in that: The preparation method comprises: The surface of the ceramic disc is modified by using a super-hydrophobic coating to obtain a super-hydrophobic ceramic disc; The surface of the super-hydrophobic ceramic disc is etched according to a preset pattern by a femtosecond laser to form a super-hydrophilic pattern area and a super-hydrophobic boundary area, thereby preparing an atomized ceramic disc with a heterogeneous wettability boundary.
2. The method according to claim 1, characterized in that Calculated by mass percentage, the super hydrophobic coating comprises: Liquid adhesive 1~1.5%; Hydrophobic SiO2 nanoparticles 1~3%; Alcohol or ester solvents 95.5~98%, totaling 100%.
3. The preparation method according to claim 1 or 2, characterized in that: The method of modifying the ceramic disc by using a super hydrophobic coating comprises: The ceramic disc is immersed in the super-hydrophobic coating for 1 min to 5 min to form a super-hydrophobic layer on the surface of the ceramic disc, and a super-hydrophobic ceramic disc is obtained after drying.
4. The preparation method according to claim 3, characterized in that: The difference between the diameter of the ceramic disc and the diameter of the pattern area is 3-10 mm; The preset pattern includes any one of a sawtooth circle structure, a circular structure, a sharp blade structure, a gradually pointed blade structure, a blunt-pointed blade structure, and a round-pointed blade structure.
5. The preparation method according to claim 4, characterized in that: The ratio of the circumference of the ceramic disc to the number of teeth in the sawtooth circle structure is 3-4:
1.
6. The preparation method according to claim 4, characterized in that: The material of the ceramic disc is selected from any one of aluminum oxide, silicon nitride, silicon carbide and zirconium oxide.
7. The preparation method according to claim 1, characterized in that: The static contact angle of the super-hydrophobic boundary area is 150-160°C. The static contact angle of the super-hydrophilic pattern area is 0~5°C, The thickness difference between the super-hydrophobic boundary area and the super-hydrophilic pattern area is 1-2 μm.
8. The method according to claim 1, characterized in that The femtosecond laser has an air jump speed of 200-500 mm / s, a marking speed of 1000-3000 mm / s, a scanning interval of 10-30 μm, a turning delay of 5-20 μs, a frequency of 500-1000 KHz, a power of 2-6 W, and a scanning number of 5-10 times.
9. An atomized ceramic disc prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The atomized ceramic disc has a super-hydrophilic pattern region and a super-hydrophobic boundary region.
10. The alumina atomizing disk according to claim 9, characterized in that: The average particle size of the atomized droplets of the atomized ceramic disc is 300-400 μm.